Comprehensive Tax Reform : The Colombian Experience - Shome, Parthasarathi (Occasional Papers; Occasional Paper ;, 1995)
This paper analyzes particular areas of tax policy that have concerned the Colombian authorities during the 1990s, while comprising a comprehensive approach to tax reform over time. It is intended to allow the reader to view in technical detail the type of analysis conducted in a representative tax reform study carried out by the IMF.